Structural Phase Transition from Tin (IV) Sulfide to Tin (II) Sulfide and the enhanced Performance by Introducing Graphene in Dye-sensitized Solar Cells. (10th September 2015) - Yang, Bo; Chen, Peng; Zuo, Xueqin; Zhou, Lei; XiaoYang,; Li, Guang; Wu, Mingzai; Ma, Yongqing; Jin, Shaowei; Zhu, Kerong
Graphical abstract: Highlights: Structural phase transition was applied to the fabrication of counter electrodes. Tin (IV) sulfide transformed into tin (II) sulfide after an annealing process. By introducing the reduced graphene oxide, the nanocomposite exhibited excellent performance. A superior power conversion efficiency of 7.47% was achieved. Abstract: Annealing is an important process for fabricating counter-electrodes of dye-sensitized solar cells. Along with the annealing process, however, structural phase transitions sometimes occur, which have significantly effect on the performance of the electrodes and cells, but is often ignored. Here, we report such a phase transition in which tin (IV) sulfide is transformed into tin (II) sulfide after annealing in an argon atmosphere. The precursor and final product are respectively fabricated together with reduced graphene to form nanocomposites that are subsequently used as the counter-electrodes. It is found that the power conversion efficiency of dye-sensitized solar cell with the counter-electrode made of tin (II) sulfide and reduced graphene oxide nanocomposites achieves 7.47%. The efficiency is much higher than that (5.30%) of a device using tin (IV) sulfide and reduced graphene oxide nanocomposites as counter-electrode and is even comparable to the value (7.75%) of a cell with conventional platinum as counter-electrode.